Study of serum leptin levels in patients with type 2 diabetes mellitus at a tertiary care centre of central India - Lohokare, Rajeev; Bansal, Akash; Kothari, Vinita; Dey Sarkar, Purnima; Gupta, Amita (International Journal of Medical Research and Review, 2016)
Background: It has been reported that Insulin and leptin share a common central signaling pathway and there might be a possible role of leptin in the etiology of type 2 DM. Studies regarding role of leptin in type 2 DM in central India are lacking. Aim: This study was conducted with the aim of comparing leptin levels in patients with type 2 DM with apparently healthy controls. Subjects and Methods: A total of 80 subjects including 40 patients of type 2 DM attending outdoor clinics of MY Hospital and 40 age and sex matched healthy controls. Fasting venous blood sample was analysed for leptin, total cholesterol (TC), triglycerides (TG), HDL-C and fasting blood sugar (FBS). Statistical analysis was performed using SPSS software version 14. Results: Mean BMI of diabetic group was 32 ± 3.48kg/m2 and that of control group was 28 ± 2.56kg/m2. Leptin levels among diabetic cases were 29.3± 19.3 ng/ml and in non diabetic subjects it was 34.8 ±21.4 ng/ml. The difference in leptin levels between cases and control were statistically significant. Conclusion: Low leptin levels are associated with type 2 diabetes mellitus independent of changes in BMI.